Bioactive Triterpenoids from the Leaves and Twigs of Lithocarpus litseifolius and L. corneus - Cheng, Yuan-Bin; Liu, Fan-Jin; Wang, Chih-Hsin; Hwang, Tsong-Long; Tsai, Yung-Fong; Yen, Chia-Hung; Wang, Hui-Chun; Tseng, Yen-Hsueh; Chien, Ching-Te; Chen, Yi-Ming Arthur; Chang, Fang-Rong; Wu, Yang-Chang (Planta Medica, 2018)
Phytochemical investigation of the leaves and twigs of Lithocarpus litseifolius and Lithocarpus corneus resulted in the isolation of four new triterpenoids (1–4), three triterpenoids (5–7) isolated from a natural source for the first time, and six known compounds (8–13). In addition, four known triterpenoids (14–17) were isolated from L. corneus. Compound 1 is a 3,4-seco-lupane-type triterpenoid, and compounds 2–4 are lupane-type triterpenoids in different oxidation states. The structures of all isolated compounds were identified by spectroscopic methods, especially NMR and mass spectrometry data. The absolute configuration of 2 and 3 was confirmed by X-ray single crystallographic analysis. The anti-inflammatory activities of 1–17 and anti-HIV activities of 2–17 were evaluated. Among them, 3-epi-betulinic acid (8) showed a strong anti-HIV activity comparable to abacavir, a drug used for treating HIV/AIDS. 3,4-seco-4(23),20(29)-lupadiene-3,28-dioic acid (5) exhibited potent inhibition of superoxide-anion generation with 86.9 ± 2.8% inhibition at 1 µM.
Keywords: Lithocarpus litseifolius; Lithocarpus corneus; Fagaceae; triterpenoids; anti-inflammatory; anti-HIV